Skin infection by larva migrans and scabies mites: case reports on unusual skin localizations - Alessandro Martella (Dermatology Reports)
Unusual skin infection localization represents a challenge to physicians regarding presentation and mode of acquisition, all of which might influence the diagnosis. At the same time, the administration of incorrect drugs due to a misdiagnosis might have a negative impact on the disease course. This article presents two case reports detailing the unusual presentation of larva migrans and scabies mites infection in two Italian patients, highlighting the importance of clinical vigilance and comprehensive evaluation of patients. These cases suggest how an accurate diagnosis requires a high index of suspicion and appropriate diagnostic tools, such as dermoscopy, for the prompt recognition of skin infections and the consequent optimal patient outcome.